Peran Kepala Sekolah dalam memenejerial kurikulum di Madrasah Tsanawiyah (MTs) Samailul Huda, Demak - As’ad; Fatimah (PT. Lancar Media Komunikasi, 2023)
The purpose of this study was to analyze the role of the school principal in managing the curriculum at Madrasah Tsanawiyah (MTs) Samilul Huda, Mlaten Village, Mijen District, Demak Regency. This research uses a qualitative approach and the method used is a case study (case study) which aims to photograph events, facts, data, and incidents regarding the management of the curriculum in the school. The data source of the research is the principal askey informan (main source) and all MTs Samailul Huda teachers. As for the technique and procedure of data collection, it is done through in-depth interviews (in depth interview), observations or observations of researchers in activities in the field, and analysis of documents related to the object of this research. The results of the study can be concluded that there are three roles that are quite effective for the principal in managing the curriculum (1) planning consisting of technical and teacher understanding, (2) implementing the curriculum in class learning (3) and evaluating learning outcomes and class learning.